Ideal conducting polymer anode for perovskite light-emitting diodes by molecular interaction decoupling. (June 2019) - Jeong, Su-Hun; Kim, Hobeom; Park, Min-Ho; Lee, Yeongjun; Li, Nannan; Seo, Hong-Kyu; Han, Tae-Hee; Ahn, Soyeong; Heo, Jung-Min; Kim, Kwang S.; Lee, Tae-Woo
Abstract: An ideal conducting polymer anode (CPA) in organic and perovskite light-emitting diodes (LEDs) requires high electrical conductivity κ, high work function WF, and prevention of exciton quenching between an anode and an overlying emitting layer. However, increasing the κ and WF at the same time has been a very challenging unsolved issue due to their trade-off relationship: previous approaches to increase the WF have reduced the films' κ and vice versa. Therefore, delicate molecular scale control of the conducting polymer compositions are required to solve this fundamental issue. Here, we introduce an effective molecular scale control strategy to decouple the WF with κ in a CPA while maintaining blocking capability of exciton quenching. This change resulted in a high current efficiency up to 52.86 cd A −1 (10.93% ph el −1 ) in green polycrystalline perovskite LEDs. Our results provide a significant clue to develop effective CPAs for highly-efficient organic and perovskite LEDs. Graphical abstract: Image 1 Highlights: Ideal conducting polymer anode with high work function and conductivity for high-efficiency perovskite LED is introduced. Molecular scale control is introduced to decouple the work function with conductivity in a conducting polymer anode. We achieved a high-efficiency polycrystalline perovskite LEDs with an external quantum efficiency of 10.93%.